2005
DOI: 10.1063/1.1979479
|View full text |Cite
|
Sign up to set email alerts
|

Orientational order and finite strain in nematic elastomers

Abstract: Nematic elastomers exhibit large, spontaneous shape changes at the transition from the hightemperature isotropic phase to the low-temperature nematic phase. These finite deformations are studied here in the context of a nonlinear, properly invariant, variational theory that couples the orientational order and elastic deformation. The theory is based on the minimization of a freeenergy functional that consists of two contributions: a nematic one due to the interaction of the mesogenic units and an elastic one a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
14
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 30 publications
0
14
0
Order By: Relevance
“…However, the measurements described above clearly show that c c 44 is neither zero nor small, but of the order of the other elastic moduli, and therefore it is not appropriate to use it as a small perturbation. This conclusion does not come as a surprise, since recently Fried and Sellers 55,56 have shown that the neo-classical Gaussian chain model 30,44,45 is incomplete and needs substantial modifications that render c c 44 to be finite. Some time ago it has been shown 31,57 that isotropic solids that undergo a spontaneous change into an anisotropic state must have a zero shear modulus c c 44 due to the Goldstone theorem.…”
Section: Soft Elasticitymentioning
confidence: 97%
“…However, the measurements described above clearly show that c c 44 is neither zero nor small, but of the order of the other elastic moduli, and therefore it is not appropriate to use it as a small perturbation. This conclusion does not come as a surprise, since recently Fried and Sellers 55,56 have shown that the neo-classical Gaussian chain model 30,44,45 is incomplete and needs substantial modifications that render c c 44 to be finite. Some time ago it has been shown 31,57 that isotropic solids that undergo a spontaneous change into an anisotropic state must have a zero shear modulus c c 44 due to the Goldstone theorem.…”
Section: Soft Elasticitymentioning
confidence: 97%
“…[80][81][82][83] Its theoretical explanation for these materials is that the energy is minimized by passing through a state exhibiting a microstructure of many homogeneously deformed parts. 38,53,81,[84][85][86][87] A natural question is then: How does soft elasticity depend on the material parameters? For simplicity, we selected an incompressible neo-Hookean-type strain-energy function, 88 where the superscript "T" represents the transpose operator, "tr" denotes the trace operator, and µ (1) ≥ 0 is constant, together with the neoclassical strain-energy function 38,51,53 with µ (2) ≥ 0 constant.…”
Section: Soft Elasticity and Stress Plateausmentioning
confidence: 99%
“…Early experimental investigations of this phenomenon, known as soft elasticity [87,110,113], were reported in [33,60,103,126]. Its theoretical explanation is that, for these materials, the energy is minimized by passing through a state exhibiting a microstructure of many homogeneously deformed parts [23,28,30,[38][39][40]60]. A natural question is then: How does soft elasticity depend on the material parameters?…”
Section: Soft Elasticity and Stress Plateausmentioning
confidence: 99%